Evolution of limb bone loading and body size in varanid lizards - Clemente, C.; Withers, Philip; Thompson, G.; Lloyd, D. (The Company of Biologists Ltd., 2011)
Geometric scaling predicts that stresses on limb bones and muscles should increase with body size. Mammals counter this sizerelated increase in stress partially through changes in bone geometry, but largely through changes in posture, with larger species having a more erect stance. However, the ability to counter size-related stresses in this fashion may be limited to those taxa that have a parasagittal gait (such as mammals), where legs are swung underneath the body. We examined locomotor kinematics for 11 species of varanid lizards (from 0.04 to 8.kg body mass) that have a sprawling gait, to determine how they moderate size-related stresses. Posture, as indicated by femur adduction and hip heights, did not change significantly with body size, beyond that expected from geometrical scaling. Instead, lizards mitigated size-related increases in stress by increasing duty factor and possibly reducing femur rotation. Incorporating these factors in biomechanical models predicted that both bending (8 M 0.016, where M is mass) and torsional (8 M -0.049) stresses should be nearly independent of body size over the size range examined. However, increasing duty factor and reducing femur rotation probably have deleterious effects on speed, and this difference in kinematics with size may explain why speed scales lower for sprawling lizards than for parasagittal mammals (8M 0.17 and 8M 0.24, respectively). Further, paralleling conclusions for the synapsid lineage, these findings suggest that evolution from sprawling to upright posture did not occur in archosaurs as a response to larger size; rather, these archosaurs likely became upright first and larger later. © 2011. Published by The Company of Biologists Ltd.